Adipose Stem Cell-Based Treatments for Wound Healing - Zeng, Ning; Chen, Hongbo; Wu, Yiping; Liu, Zeming (Frontiers in Cell and Developmental Biology, 2022)
Wound healing is one of the most complex physiological regulation mechanisms of the human body. Stem cell technology has had a significant impact on regenerative medicine. Adipose stem cells (ASCs) have many advantages, including their ease of harvesting and high yield, rich content of cell components and cytokines, and strong practicability. They have rapidly become a favored tool in regenerative medicine. Here, we summarize the mechanism and clinical therapeutic potential of ASCs in wound repair.